A new species of Philodendron subg. Pteromischum (Araceae) from the Paraná River, Brazil - Buturi, Camila Vanessa; Temponi, Lívia Godinho; Sakuragui, Cassia Mônica (Phytotaxa, 2015)
A new species of Philodendron subg. Pteromischum was found growing along the Paraná River and it is here described and illustrated. Philodendron rheophyticum is similar to P. flumineum from which it differs by its obscure lateral veins, by having an obovate leaf blade, longer spadix and pistils with 3-4 locules. Philodendron rheophyticum is also similar to P. sonderianum but from which it can be distinguished by its obscure primary lateral veins, by having upright closed sheath, obovate leaf shape, longer length of spathe and petiole.